Communication Barriers between Teachers and Students in Online Learning Process in the Time of the Covid-19 Pandemic (Case Study at Private Private Junior High School) - Yeni Saufina Siregar; Djoharis Lubis; Nathanael Sitanggang (BIRCU, 2021)
Corona virus (corona virus disease/Covid-19) a name given by the World Health Organization (WHO) to patients with 2019 corona virus infection which was first reported from the city of Wuhan, China at the end of 2019. In several educational institutions starting from the school level elementary through college take online distance learning alternatives. Online learning is a new thing in the implementation of the learning process for educators and students. The purpose of the study is to find out what are the obstacles in communicating between teachers and students during the covid 19 pandemic. The existence of obstacles in the learning process can reduce students' interest in learning. In online learning, adequate facilities and infrastructure are needed, such as laptops, computers, smartphones, and internet networks. Communication in learning is the process of delivering a message between the teachers to students, both verbally and nonverbally, which was originally intended to make students able to understand the material and the teacher's message conveyed. The online learning model that is the choice of teachers is to use the WhatsApps facility where the teacher creates WhatsApp groups so that all students are involved in the group. Assignments are given via WhatsApps. Assignment collection makes it easier for students through WhatsApp messages.